A Program of Nurse Management for Unscheduled Consultations of Children With Acute Minor Illnesses in Primary Care. Issue 6 (16th October 2015) - Fabrellas, Núria; Juvé, Eulàlia; Solà, Montserrat; Aurín, Eva; Berlanga, Sofia; Galimany, Jordi; Berenguer, Lidia; Pujol, M. Cèlia; Lacuesta, Sara; Villo, M. Cinta; Torres, Montserrat
Abstract: Introduction: Attention to patients with acute minor illnesses represents a major burden for primary care. Although programs of nurse care for children with acute minor illnesses in primary care started a long time ago, there is limited information about the results of these programs in current practice. Objectives: The objective of this study was to assess the feasibility and efficacy of a program of nurse management for unscheduled consultations of children with acute minor illnesses. Methods: Observational study of children seeking unscheduled consultations for 16 acute minor illnesses in 284 primary care practices during a 2‐year period. The program of nurse management used predefined management algorithms. Findings: Among 467, 160 consultations performed, case resolution was achieved in 65.4%. The remaining 34.6% of cases were not solved by the primary healthcare nurse due to the existence of signs of alarm and were referred to a pediatrician. Return to consultation during a 7‐day period for the same reason as the original consultation was only 2.6%. Conclusions: A program that uses management algorithms is effective for nurse care management of children with acute minor illnesses in primary care. Clinical Relevance: Application of programs of nurse management for unscheduled consultations for children with acute minor illnesses is feasible and effective.